Viabilidade econômica do cultivo de frutíferas nativas em áreas degradadas e de preservação permanente - Lorencett, Fernando Roberto (2011)
Brazilian law imposes restrictions on the use of Permanent Preservation Areas (APP) for agriculture, is necessary to find economically viable alternatives and appropriate environmental legislation. Several family farms are at risk of becoming unviable, the constraints faced by virtue of its location next to rivers, areas of steep slopes or to their own water sources. In the Far-west region of Santa Catarina, various properties which are located at considerable APPs include spaces. Farmers face difficulties in getting the properties become economically viable to produce plots that are left over from the preservation of the PPAs. The objective of this study was to analyze the economic feasibility of growing fruit native APP or degraded areas. Determining the cost of production of the following native fruit species occurring in the region: Jabuticaba (Myrciaria cauliflora (Mart.) O. Berg), Pitanga (Eugenia uniflora L.), cherry (Eugenia involucrata DC.) Araticum and (Annona neosalicifolia H. Rainer). It was considered that the cost seeds and seedlings represent the total production cost for the analysis. We also analyzed the profitability of this type of cultivation compared to APP and profitability from two fruit (peach and orange) and an annual crop (soybean). It was found that these native fruit production is more feasible from seed, mainly due to the price of seedlings is high. The profitability of native fruit is bigger than the orange plantations, and smaller than the peach. The comparison with the soybean crop in the same area, considering the regional technology used showed greater viability in the native fruit.